4k+13=7-2k

Simple and best practice solution for 4k+13=7-2k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4k+13=7-2k equation:


Simplifying
4k + 13 = 7 + -2k

Reorder the terms:
13 + 4k = 7 + -2k

Solving
13 + 4k = 7 + -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
13 + 4k + 2k = 7 + -2k + 2k

Combine like terms: 4k + 2k = 6k
13 + 6k = 7 + -2k + 2k

Combine like terms: -2k + 2k = 0
13 + 6k = 7 + 0
13 + 6k = 7

Add '-13' to each side of the equation.
13 + -13 + 6k = 7 + -13

Combine like terms: 13 + -13 = 0
0 + 6k = 7 + -13
6k = 7 + -13

Combine like terms: 7 + -13 = -6
6k = -6

Divide each side by '6'.
k = -1

Simplifying
k = -1

See similar equations:

| 2x+20=11x-70 | | u^2+7u-2=0 | | -.6666x=.8888 | | 5=(-16)p | | -14x=14 | | b^3+49b=0 | | 5=16p | | (20+p)*3+p= | | 20+p*3= | | 20+p*3+p= | | x^3+8x=6x^2 | | (x+4)(x+8)=1 | | 7x^2-11=28x+86 | | 12x-15=4x+25 | | 2*3-(8-1)+4+3*(2+1)-7+4-(4+8)=851 | | X^3-12x+10=0 | | 2*3-(8-1)+4+3*(2+1)-7+4-(4+8)= | | 40x^3+43x^2=6x | | 2d-1=6d+1 | | 18=-12+19 | | x^2-8=-12 | | 6k+3=6k-3 | | 5(x-4)-3(1-2x)= | | (x+1)(x+3)=9 | | 2x^2-72=8x+45 | | 2u^2=5u+3 | | 9x^2+12x+4=24 | | (x+7)(x-5)=13 | | 5p^2+28p+15=0 | | 165-5x=22x+15 | | -8z-3z=24-3 | | 14+-8x=59+-29x |

Equations solver categories